A pro-active approach in managing housing defects: a way of producing a quality house / Noor Anisah Abdullah, Shahela Mamter and Mohd Esham Mamat - Abdullah, Noor Anisah; Mamter, Shahela; Mamat, Mohd Esham (2021)
Housing defects is a common problem that occurred in housing construction. It is important to ensure a good quality of housing product to fulfil the user’s satisfaction. Existing studies have determined the common problem causes of housing defects in Malaysia. This research aimed to establish the housing defects causes of undiscovering present finding housing defects issues in the housing construction industry. The research objectives were to identify the causes of housing defects and to analyze the pro-active measures in managing housing defects to produce a quality house. This research is done through literature review, supported by a questionnaire survey. This study found that most significant causes of housing defects were due to human error, listed as the quality of contractors, lack of experience and competency of labour or poor workmanship and lack of supervision and quality control. The research also evaluated the most pro-active approach in managing housing defects was by proper manpower management. From the research findings, it can be concluded that the occurrence of housing defects can be minimized through the proper manpower management to produce a quality house.